PENENTUAN REFERENCE VALUE DAN KANDUNGAN KADMIUM TANAH PADA AREAL PERTANIAN DI KECAMATAN PONTIANAK UTARA - Rini Susana (Purifikasi, 2010)
This research is aimed to find out total cadmium content in soil at various usage of agricultural land areas at Sub-district North Pontianak and to determine the reference value of cadmium in agricultural soils. Thirty soil samples were collected using purposive sampling technique. Sample collection was carried out through composite technique. The samples were taken on surface soil layer at 0-20 cm deep. Interview was done to determine the duration of land usage and application of chemicals in farming input activities. Respondents were determined randomly to farmers of 4 kinds of farm land uses (paddy, vegetables, papaya and Aloe vera). Each group of farmers comprised 10 respondents. Analysis of soil samples of this research covered: texture, organic matter and total cadmium content. Data analysis was performed using descriptive analysis. The results showed that the reference value of cadmium ranged from 1.10 to 2.46 mg/kg. The reference value of peat soil higher than that on alluvial. Total cadmium content of agricultural land areas in Sub-district North Pontianak ranged from 0.009 to 0.601 mg/kg, which was still below the maximum reference value. Sources of cadmium in peat soil are fosfat fertilizer and wood ash applications. Wood ash is applied for improving soil pH. The presence of cadmium in aluvial soil is predicted from river sediment.